Gerakan Pesantren Kombos di Manado dalam Merespon Arus Post-Nasionalisme - Almunawar Bin Rusli (IAIN Manado, 2016)
Pesantren Kombos was established in 1977. From the new order era to reformation, pesantren Kombos have contributed to socio-religious life in multicultural society in Manado (Islam 128.483 %, Christian 254.912 %, Catholic 20.602 %, Hindu 692 %, Buddha 2.224 %, and Konghucu 499 %). Since the 9/11 attacks in the United States and the Bali bombings in October 2002 in Indonesia, pesantren have been the focus of international attention. Foreigner called Islamic education as breeding grounds for terrorist. Acts of radicalism and terrorism (postnasionalism) commited by Abu Bakar Baa’syir and Abdullah Sungkar has made pesantren become training institutions of jihad against the West under Jamaah Islamiyah group as Sidney Jones’s observation. Other religions are taught from the perspective of a particular religion. This model of religious education has been challenged especially after the 1998 political reform. Through literature study, the result of this research indicates that the situation in Manado looks stable even not trapped in actions of radicalism and global terrorism. To respond postnasionalism, pesantren Kombos in Manado build three major movements, namely ideology-political movement, demographic-accomodative movement, and programmatic-assosiative movement. Those three movements are using humanist, rational, and functional approach. Thus, in summary, pesantren Kombos has a cosmopolitan character that is actualized in the system Torang Samua Basudara and Si Tou Timou Tumou Tou.Keywords : Movement, Pesantren Kombos, Postnasionalism